A revision of the Aiphanes parvifolia complex (Arecaceae) - Bernal, Rodrigo; Borchsenius, Finn; Hoyos-Gómez, Saúl E.; Manrique, Héctor Favio; Sanín, María José (Phytotaxa, 2019)
Recent field work and the study of new collections have revealed that the Andean palm Aiphanes parvifolia, as interpreted in the most recent monograph of the genus, actually included five species. Three of them, Aiphanes decipiens, Aiphanes gloria and Aiphanes tatama, whose specimens were previously considered as A. parvifolia, are described here as new, and another one, also formerly treated as A. parvifolia, was recently described as Aiphanes argos. Two additional species, not collected before, belong also to this complex and are described here as new: Aiphanes bio and Aiphanes cogollo. The true Aiphanes parvifolia is recircumscribed, and the current neotype is superseded. A taxonomic treatment of all the species in the group is presented, including detailed descriptions and illustrations, and a key to identify them. Six of the species are categorized as Critically Endangered and one as Endangered, based on IUCN criteria.